Development of an Accident Prevention and In-School First Aid Training Program for Kindergarten Teachers - Konthon, Phattharakorn; Thanawan, Wacharawan; Damna, Kanyarat; Kringkrathok, Pattaraphon; Torcheewee, Pranpriya; Aodsumrong, Sawitre; Julsumrong, Pemika; Butchanon, Virawat; Niyomsat, Yapat (Ramathibodi Medical Journal, 2025)
Background: Despite being preventable, injuries in children are continuously increasing. This issue has become a significant and urgent global concern, necessitating studies and the development of systems for accident prevention and first aid for caregivers. Such measures could significantly reduce disability and premature mortality among children. Objectives: To develop and evaluate the effectiveness of a program for early childhood accident prevention and first aid training, specifically for teachers, using an online learning material. Methods: The sample consisted of 43 kindergarten teachers in Nakhon Ratchasima province, assigned to an interview group (n = 10) and an efficiency testing group (n = 33) selected through multistage sampling. The research instruments included an interview on accident prevention and basic first aid, a pre- and post-knowledge assessment, a questionnaire assessing satisfaction with the platform, and online learning material from LINE official Pre-Hosp for Kid. Data was analyzed using descriptive statistics. Results: The developed online learning platform was highly effective (mean [SD], 4.38 [0.62]). The platform’s efficiency was 81.67/88.89, meeting the established criteria (80/80). The effectiveness index was 0.39, indicating that kindergarten teachers’ knowledge of accident prevention and first aid increased by 39% after using the online learning material. Conclusions: This study showed that the program is highly suitable for enhancing knowledge in accident prevention and first aid for kindergarten teachers.